Wound Device: Study and development of device for wound indicators towards VR-Technology - Albråten, Karin (My University, 2023)
This report covers the work that have been done in the Master Thesis project at Mas ter Program Product Development at Chalmers University of Technology. This includes the product development process, from idea to finished prototype, of a device that can measure wound indicators such as applied pressure and possibly send data to computer via Bluetooth protocol. It also includes research of different methods and tools used in emergency healthcare exercises within the Police, Military and Home Guard in Sweden together with result from several interviews with representatives in these different organ isations as well as conducted experiments of final concept and description of developed prototype.
Keywords: Wound Indicators, Emergency Healthcare, Bluetooth Low Energy (BLE), Smart Tourniquet, Force Sensing Resistor, Microcontroller